Research progress on the development of pennycress (Thlaspi arvense L.) as a new seed oil crop: a review - Ma, Jianyu; Wang, Haoyu; Zhang, Yuhong (Frontiers in Plant Science, 2023)
Compared with other crops, pennycress (Thlaspi arvense L.) is a niche emerging oil crop. In recent years, research on pennycress has been increasingly reflected in various directions. Pennycress belongs to the Brassicaceae family and was introduced from Eurasia to North America. It has been found worldwide as a cultivated plant and weed. In this paper, we review the advantages of pennycress as a supplementary model plant of Arabidopsis thaliana, oil and protein extraction technology, seed composition analysis based on metabolomics, germplasm resource development, growth, and ecological impact research, abiotic stress, fatty acid extraction optimization strategy, and other aspects of studies over recent years. The main research directions proposed for the future are as follows: (1) assemble the genome of pennycress to complete its entire genome data, (2) optimize the extraction process of pennycress as biodiesel, (3) analyze the molecular mechanism of the fatty acid synthesis pathway in pennycress, and (4) the functions of key genes corresponding to various adversity conditions of pennycress.